366 days in Abraham Lincoln's presidency : the private, political, and military decisions of America's greatest president - Wynalda, Stephen A. (Skyhorse Pub., 2010)
Journalist Stephen A. Wynalda has constructed a painstakingly detailed day-by-day breakdown of president Abraham Lincoln's decisions in office--including his signing of the Homestead Act on May 20, 1862; his signing of the legislation enacting the first federal income tax on August 5, 1861; and more personal incidents like the day his eleven-year-old son, Willie, died. Revealed are Lincoln's private frustrations on September 28, 1862, as he wrote to vice president Hannibal Hamlin, "The North responds to the [Emancipation] proclamation sufficiently with breath; but breath alone kills no rebels." --from publisher description